2019
DOI: 10.1097/wnp.0000000000000577
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Signal Characteristics of Electrocorticography and Stereoelectroencephalography: The Effect of Contact Depth

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 36 publications
4
14
0
Order By: Relevance
“…A higher depth means the contact is deeply embedded within WM and has little surrounding GM tissue) 5,6 . Alternative definitions have shown similar results when comparing GM and WM signals in previous studies 6 , however, we still provide complimentary analyses using both definitions here. We found that both distance from GM ( p < 5 x 10 −10 ) and WM depth ( p < 0.05) are still significantly related to FC (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A higher depth means the contact is deeply embedded within WM and has little surrounding GM tissue) 5,6 . Alternative definitions have shown similar results when comparing GM and WM signals in previous studies 6 , however, we still provide complimentary analyses using both definitions here. We found that both distance from GM ( p < 5 x 10 −10 ) and WM depth ( p < 0.05) are still significantly related to FC (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The focus, instead, has been on the analysis of gray matter functional activity as it relates to neurobiology and disease, because the signals can be orders of magnitude larger (Fig. 1b-c) 46 , and gray matter is predominantly thought to be where neural computation takes place. Excitingly, some research groups have shown the existence of neuronal cell bodies in deeper white matter tissue 10 , the release of neurotransmitter vesicles in white matter 11 , and the existence of detectable white matter blood-oxygenation level dependent (BOLD) signals across a range of different tasks 12 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Intracranial stereoelectroencephalography (SEEG) and electrocorticography (ECoG) are invasive electrophysiological recordings of brain activity (Young et al, 2019 ). Although only applied to clinical populations, the direct recording from the brain tissue allows a relatively superior geographical resolution.…”
Section: Focal and Distributed Patterns Of Neural Synchrony In Behavimentioning
confidence: 99%